Phthalimide as a versatile pharmacophore scaffold: Unlocking its diverse biological activities - Fernandes, Guilherme F. S.; Lopes, Juliana R. [UNESP]; Dos Santos, Jean L. [UNESP]; Scarim, Cauê B. [UNESP] (Wiley, 2023)
Phthalimide, a pharmacophore exhibiting diverse biological activities, holds a prominent position in medicinal chemistry. In recent decades, numerous derivatives of phthalimide have been synthesized and extensively studied for their therapeutic potential across a wide range of health conditions. This comprehensive review highlights the latest developments in medicinal chemistry, specifically focusing on phthalimide-based compounds that have emerged within the last decade. These compounds showcase promising biological activities, including anti-inflammatory, anti-Alzheimer, antiepileptic, antischizophrenia, antiplatelet, anticancer, antibacterial, antifungal, antimycobacterial, antiparasitic, anthelmintic, antiviral, and antidiabetic properties. The physicochemical profiles of the phthalimide derivatives were carefully analyzed using the online platform pkCSM, revealing the remarkable versatility of this scaffold. Therefore, this review emphasizes the potential of phthalimide as a valuable scaffold for the development of novel therapeutic agents, providing avenues for the exploration and design of new compounds.
Keywords: bioactive compounds; drug design; medicinal chemistry; new drugs; phthalimide; thalidomide